(untitled) (Research, Society and Development, 2023)
Nursing professionals working in Intensive Care Units (ICUs) are often exposed to chronic stressors in the workplace, which can adversely affect their mental and physical health. Therefore, the work environment, personal and professional life trajectory of these workers directly affect the reality of care. The objective of this study was to investigate the work universe of these professionals based on variables such as working hours, function, salary, professional career, unionization, interprofessional relations, life and professional trajectory, the concept of “care” and the division of labor between men and women. For this, a research with a qualitative approach was carried out, using as a data production strategy interviews with seven nurses and one male nurse, with an average duration of 40 minutes, at a distance, using technologies such as Zoom and Google Meet, organized at from a semi-structured script. It was evident that the majority had an immense desire to serve and care for others. All interviewees stated that at the time they completed their training, there were many more women than men on the course. In addition, most claimed to have more than one workplace, mainly due to the low pay in the area and stated a series of physical and emotional problems related to work. Lack of inputs and employees in hospitals and poor qualification of part of the professional team are among other challenges faced. It is concluded, therefore, that nursing is still a neglected profession, with an immense sexual division of labor, challenges intensified during the COVID-19 pandemic.